The Effect of Technostress on Turnover Intention with Burnout as a Mediation in Gen Z in the City of Surabaya - Nanda Putri Kandita; Sarwari Sarwari; Galuh Ajeng Ayuningtiyas; Priyanto Priyanto (International Journal Business, Management and Innovation Review, 2026)
Using burnout as a mediating variable, this study looks at how technostress affects turnover intention among Gen Z workers in Surabaya. Based on the city's rapid digitization and widespread internet access, the study examines how technological advances can boost productivity and create difficulties associated with technology use. Technostress is defined as an unpleasant psychological state that results from a person's inability to adapt to the demands and advances of technology. Burnout, a condition of physical, emotional, and mental exhaustion brought on by ongoing job stress, is said to be the result of this strain for Gen Z, often known as "digital natives," who grew up with technology. Burnout can afterward result in the urge to quit. This study used a causal research design and a quantitative approach. An online survey was used to collect data, and Gen Z respondents in Surabaya were presented based on predetermined criteria, such as age and intention to utilize technology for employment. Data analysis tests the direct and indirect correlations between variables using structural equation modeling (SEM) based on Smart-PLS. The study's findings showed that technostress greatly reduces burnout. Additionally, it has been demonstrated that burnout greatly increases the intention to leave. The association between technostress and turnover intention is totally mediated by burnout, according to key findings, which means that increasing burnout fully explains how technostress affects turnover intention. The study's findings highlight the significance of organizational policies that go beyond limiting digital exposure to address burnout, particularly among Gen Z. In order to better understand the causal link and context of Gen Z's experience with technostress and burnout in an increasingly digital workplace, it is suggested that future studies employ a longitudinal gradual approach or a combination of qualitative and quantitative methodologies.